"This Is a Union of Values": The Rise of the LGBTI Rights Norm as Part of the EU's Identity Construction. (27th August 2021) - Eigenmann, Laura
Abstract: Since the early 1990s, the EU has increasingly institutionalized lesbian, gay, bisexual, transgender, and intersex (LGBTI) rights and more recently started to use them as a symbol for its modern and progressive identity. This article investigates this development, focusing on EU actors and institutions. Combining a genealogical analysis with the analysis of current discursive struggles around LGBTI rights within EU institutions, it shows that the rise of LGBTI rights is closely intertwined with the search for a common European identity, shared values, and attempts to strengthen solidarity in times when right-wing, nationalist, and Eurosceptic movements are increasingly challenging the EU's legitimacy.